The Perception of "Intelligent" Design in Visual Structure. (January 2022) - Schmidt, Filipp
Many objects in our visual environment will appear to us either as a consequence of "intelligent" design—the purposeful action of an animal mind—or as a consequence of self-organization in response to nature's forces—for example, wind or gravity. Here, the origin of this distinction is studied by collecting human judgements about skeletal representations of objects, that reduce objects to their basic visual structure. The results suggest that humans attribute an animate origin to visual objects with basic structures exhibiting straight lines and right angles.